Electrochemical property analysis of zinc vanadate nanostructure for efficient supercapacitors. (February 2020) - Ezhil Arasi, S.; Devendran, P.; Ranjithkumar, R.; Arunpandiyan, S.; Arivarasan, A.
Abstract: Nano structured zinc vanadate, Zn3 (VO4 )2, have been successfully synthesized by simple co-precipitation method and calcined at 600 °C. Calcinated Zn3 (VO4 )2 nano flakes were characterized by various analytical techniques to examine the structural, optical, and surface morphological properties. The X-ray diffraction pattern revealed that the prepared Zn3 (VO4 )2 nanoparticles were orthorhombic crystalline structure and found the crystallite structure was ~44 nm. The flake shaped Zn3 (VO4 )2 nanoparticles was evaluated by electron microscopies such as scanning electron microscopy and high-resolution transmission electron microscopy studies. Elemental compositions and functional groups were elucidated by energy dispersive spectroscopy with mapping and Fourier transform infrared spectral studies. Electrochemical behaviour of Zn3 (VO4 )2 nanostructures were investigated by cyclic voltammetry, chronopotentiometry and electrochemical impedance spectroscopic analysis. The specific capacitance value for the prepared nanoparticles was 312 Fg -1 with high retention of about 90.7% which was achieved after 5000th cycles. It clearly revealed that synthesized Zn3 (VO4 )2 nanoparticles may lead to potential application for forthcoming energy storage devices.